Pengaruh Penggunaan Platform Komunikasi Digital terhadap Hubungan Sosial Remaja di SMK Negeri 2 Binjai - Vira Ade Natasya; Sabrina Zailanty; Novia Elisa; Jelita Ananda; Cindy Amalia; Saif Eldi Hakim (Federalisme: Jurnal Kajian Hukum dan Ilmu Komunikasi, 2025)
To determine the effectiveness of using digital communication platforms on social relations among adolescents at SMK Negeri 2 Binjai is the aim of this study. Simple linear regression analysis is the method used. Simple linear regression analysis was conducted after the classical acceptance test. This is to first ensure that the model does not have problems with normality, multicollinearity, and heteroscedasticity. 30 young people from SMK Negeri 2 Binjai as the population in this study. Based on the results above, we can see that the coefficient of determination (R2) value is 0.60 or 60%. Therefore, this value means that the variables in the use of digital communication platforms have a 60% impact on social relationships, and the remaining 40% of other variables not discussed in this study are affected. To get meaning and satisfaction from digital communication, we can approach this means of interaction with intention and authenticity. Text messages are edited many times and sent to several friends to be edited before finally being sent to the recipient do not always fully represent our true feelings.